1995
DOI: 10.1108/09576069510099356
|View full text |Cite
|
Sign up to set email alerts
|

A proposed structure for distributed shopfloor control

Abstract: Discusses the movement away from hierarchical organizational structures towards flatter, heterarchical, structures which is reflected in the growing interest in distributed manufacturing control systems. Traditional hierarchical control systems are limited by the breadth, quantity and timeliness of information needed for their operation. Distributed, heterarchical, control systems overcome these hierarchical limitations but, concurrently, forfeit advantages of the hierarchy including analytically optimal loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Due to the structural rigidity of classical centralized control architectures in manufacturing, the decentralized (or heterarchical) control structure has drawn more attention (Crowe and Stahlman, 1995;Dilts et al, 1991;Duffie and Prabhu, 1994). One of the most important properties of the heterarchical structure is that the decision-making responsibilities are fully distributed to each component of the system.…”
Section: Agent-based Approachmentioning
confidence: 99%
“…Due to the structural rigidity of classical centralized control architectures in manufacturing, the decentralized (or heterarchical) control structure has drawn more attention (Crowe and Stahlman, 1995;Dilts et al, 1991;Duffie and Prabhu, 1994). One of the most important properties of the heterarchical structure is that the decision-making responsibilities are fully distributed to each component of the system.…”
Section: Agent-based Approachmentioning
confidence: 99%
“…Neither hierarchical or heterarchical systems are able to fulfil these requirements [3,4]. Hierarchical systems have a typically rigid structure which makes it very hard for them to react to turbulences in an agile way.…”
Section: Introductionmentioning
confidence: 99%
“…Holons and holarchies3 Most of the system architectures based on agents are heterarchical. Nevertheless there are also agent based systems which do not adopt heterarchical control 4. Holistic scientific paradigm focusing on the study of Complex Adaptive Systems (C.A.S.)…”
mentioning
confidence: 99%
“…Panwalker and Iskander (1977) and Blackstone et al (1982) provided oft-quoted survey articles about known research results with sequencing rules. Studies have shown that the selection of the dispatching rules has a significant impact on system performance (Crowe and Stahlman, 1995). Given its importance, extensive research has been done in identifying dispatching rules that are superior.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that a dispatching rule ordinarily sequences jobs and/or machines only according to local information of the manufacturing system, either current system states or information of a specific manufacturing resource at the decision point. Consequently it cannot guarantee globally satisfactory performance (Brennan, 2000;Crowe and Stahlman, 1995).…”
Section: Introductionmentioning
confidence: 99%